Penyusunan Buku Digital Burung Terancam sebagai Sumber Belajar Biologi SMA: (Preparation of the Digital Book of Threatened Birds as a High School Biology Learning Resource) - Elania Zoela Saputri; Destri Ratna Maâ€™rifah; Arief Abdillah Nurusman; Dwi Nugroho Adhiasto; Novi Febrianti (BIODIK, 2022)
This study aims to determine the quality of digital books of endangered birds according to the IUCN Red List at PASTY as a high school biology learning resource based on assessments by media experts, material experts, and biology teachers. In this study, the digital book compilation model was adapted from the 4D development model (define, design, develop, and disseminate). which is limited to development. The instrument used is a Likert scale assessment questionnaire sheet with scales 1-4. Product validation was carried out by media experts, namely a Biology Education lecturer, Ahmad Dahlan University, an ornithologist from the Science for Endangered and Trafficked Species (SCENTS) Foundation as a material expert , a class X biology teacher at SMA Negeri 1 Seyegan. The results of the product assessment were then analyzed descriptively. The results showed that the digital book compiled had very good quality based on assessments by media experts, material experts, and biology teachers. Key words: Learning Resources, Digital Books Â  ABSTRAK Penelitian ini bertujuan untuk mengetahui kualitas buku digital burung terancam menurut IUCN Red List di PASTY sebagai sumber belajar biologi SMA berdasarkan penilaian oleh ahli media, ahli materi, dan guru Biologi. Pada penelitian ini model penyusunan buku digital diadaptasi dari model pengembangan 4D (define, design, develop, dan dissemination) yang dibatasi sampai dengan tahap develop. Instrumen yang digunakan adalah lembar angket penilaian skala Likert dengan skala 1-4. Validasi produk dilakukan oleh ahli media yaitu dosen Pendidikan Biologi, Universitas Ahmad Dahlan, ahli burung dari Yayasan Science for Endangered and Trafficked Species (SCENTS) sebagai ahli materi, dan salah satu guru Biologi kelas X di SMA Negeri 1 Seyegan. Hasil dari penilaian produk kemudian dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa buku digital yang disusun memiliki kualitas sangat baik berdasarkan penilaian oleh ahli media, ahli materi, dan guru Biologi. Kata kunci: Sumber Belajar, Buku Digital